2023
DOI: 10.31557/apjcp.2023.24.3.1037
|View full text |Cite
|
Sign up to set email alerts
|

Study on Breast Cancer in Kazakhstan Using the Functional Time Series

Abstract: Aim:In Kazakhstan and Central Asia, breast cancer (BC) is the most common malignancy among women. However, no large-scale study on breast cancer using the functional time series approach has been carried out in Kazakhstan. Methods: A functional assessment of the age-period-cohort model (APC) and the survival rate (period 2017-2021) was used in the retrospective study. Clinical and demographic information on patients was analysed, including age, gender, region of residence, kind and stage of tumour, occupation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, the identified PVs were differentially associated with biomarkers and prognostic factors. Since the average incidence in young women of all ethnicities in Kazakhstan is 329.6 cases per year [ 1 ], we have every reason to discuss the applicability of the results to the general population and the sufficient representativeness of our sample, consisting of 224 young Kazakh women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the identified PVs were differentially associated with biomarkers and prognostic factors. Since the average incidence in young women of all ethnicities in Kazakhstan is 329.6 cases per year [ 1 ], we have every reason to discuss the applicability of the results to the general population and the sufficient representativeness of our sample, consisting of 224 young Kazakh women.…”
Section: Discussionmentioning
confidence: 99%
“…In Kazakhstan, breast cancer (BC) is the most common malignancy in women. According to the latest national study on the epidemiology of BC in Kazakhstan, the number of reported cases increased by 14% between 2017 and 2021 [ 1 ]. By nationality, most BC patients with a confirmed primary diagnosis are Kazakh (48.1%), followed by Russian (33.1%) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer (BC), cervical cancer (CC), and prostate cancer (PC) are serious public health problems in many countries, including Kazakhstan (Pak et al, 2021, Shertaeva et al, 2023, Gassanov et al, 2020. Cancer ranks as the first or second leading cause of premature Screening is the primary tool for early detection and reduction of cancer mortality (Hall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%